DETERMINANTS OF CUSTOMER TRUST IN RURAL E-COMMERCE IN ZHENGZHOU, CHINA: A CASE STUDY OF TAOBAO VILLAGES - Lyu, Jingwen; Ratasuk, Akaraphun (วารสารปัญญาภิวัฒน์, 2024)
Trust is the potential key to unlocking the competitiveness of online businesses. Building trust can help businesses maintain long-term relationships with their stakeholders. This research studied the effects of marketing factors, including product quality, service quality, security, reputation, ease of use, and usefulness, on customer trust and the mediating role of customer satisfaction in the rural e-commerce businesses in Zhengzhou, China, based on the foundation of the social exchange theory. Self-administrative questionnaires were used to gather survey data from 420 Taobao Village customers. The PLS-SEM results showed that perceived security, perceived reputation, perceived ease of use, and perceived usefulness directly affected customer trust. In addition, the Sobel test results illustrated that customer satisfaction mediated between all but perceived usefulness and customer trust. The findings provided new insights into the roles of these marketing factors in fostering customer trust directly and indirectly through customer satisfaction and an expansion to the application of the social exchange theory, especially in the rural e-commerce business.